ANALISIS LAPORAN KEUANGAN DITINJAU DARI RASIO LEVERAGE DAN RASIO PROFITABILITAS DI KOPERASI RUKUN KARYA LUBUKLINGGAU TAHUN 2012-2017 - Fitria Fitria; Agustinus Samosir; Masayu Putri Sundari (LPPM UNIVERSITAS BINA INSAN, 2018)
ABSTRACT This study aims to analyze financial statements using Leverage Ratios (Debt to Assets and Debt to Equity) and Profitability Ratios (Return on Assets and Return on Equity). The Rukun Karya Lubuklinggau Cooperative is located at Jalan Letkol Surkino Rt. 16 No. 55 Air Kuti Sub-District of Lubuklinggau Timur I Sub-District, Lubuklinggau City. This study uses the financial statements of Balance Sheet and Profit and Loss then analyzed using financial ratios based on the Regulation of the State Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 06 / Per / M.KUKM / V / 2006 concerning guidelines for research on outstanding cooperatives. The results of this study indicate the calculation of the 2012 Leverage (Debt to Assets) ratio of 61%, which means 25 (Unhealthy), in 2013 amounted to 61% value 25 which means (Unhealthy), 2014 amounted to 60% value 50 which means ( Unhealthy), 2015 amounted to 61% of its value 25 which means (Unhealthy), in 2016 amounted to 59% of its value 50 which means (Unhealthy), in 2017 amounted to 59% of value 50 which means (less healthy). Calculation of the 2012 Debt to Equity ratio of 162% is worth 25 which means (Unhealthy), in 2013 amounted to 158% of its value 25 which means (Unhealthy), in 2014 amounting to 155% of value 25 which means (Unhealthy), 2015 amounted to 158% of its value 25 which means (Unhealthy), in 2016 amounted to 147% of its value 50 which means (Unhealthy), in 2017 amounting to 148% the value is 50 which means (less healthy). The 2012 Profitability Ratio (Return on Assets) of 4% is worth 50, which means (Unhealthy), in 2013 amounting to 4% value 50 which means (Unhealthy), in 2014 amounted to 4% value 50 which means (less healthy), in 2015 amounted to 4% the value of 50 which means (Unhealthy), in 2016 amounted to 4% the value of 50 which means (less healthy), in 2017 amounted to 4% of its value 50 which means (less healthy).